Recent advances in the genetics of language impairment. - Newbury, D; Fisher, S; Monaco, A (2010)
Specific language impairment (SLI) is defined as an unexpected and persistent impairment in language ability despite adequate opportunity and intelligence and in the absence of any explanatory medical conditions. This condition is highly heritable and affects between 5% and 8% of pre-school children. Over the past few years, investigations have begun to uncover genetic factors that may contribute to susceptibility to language impairment. So far, variants in four specific genes have been associated with spoken language disorders - forkhead box P2 (FOXP2) and contactin-associated protein-like 2 (CNTNAP2) on chromosome7 and calcium-transporting ATPase 2C2 (ATP2C2) and c-MAF inducing protein (CMIP) on chromosome 16. Here, we describe the different ways in which these genes were identified as candidates for language impairment. We discuss how characterization of these genes, and the pathways in which they are involved, may enhance our understanding of language disorders and improve our understanding of the biological foundations of language acquisition.